The Relationship Between Religious Literacy and Scientific Attitude and Their Impact on Islamic Religious Education Learning Outcomes in High Schools - Nanang Qosim Al Masquri; Sukarno; Alfian (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to examine the relationship between religious literacy and scientific attitudes to the learning outcomes of Islamic religious education in Sekolah Menengah Atas Negeri 13 Kota Jambi. This study uses a quantitative research method. The population in this study was 179 students, and we used purposive sampling techniques to select a research sample from 124. Data collection techniques include tests, questionnaires, and documentation. The findings of the study showed that: 1) The relationship of religious literacy to the learning outcomes of Islamic Religious Education obtained a value of 0.404 > 0.05, meaning that there was no significant relationship between the religious literacy variable and the Islamic Religious Education learning outcome variable; 2) The relationship of scientific attitudes on the learning outcomes of Islamic Religious Education obtained a Sig. Value of 0.914 > 0.05, meaning that there was no significant relationship between the variables of scientific attitudes and the variables of Islamic Religious Education learning outcomes; 3) Religious literacy and scientific attitude simultaneously obtained a Sig. F change value of 0.667 > 0.05, meaning that it did not have a significant relationship to the learning outcomes of Islamic Religious Education. Furthermore, this study does not address the other variables that account for the remaining 99.3% of the simultaneous relationship, resulting in a confidence level of 0.7%.